Implementation of the Public Market Revitalization Policy at Karah Baru Market, Surabaya City - Nadia Putri Ananta; Tauran T; Tjitjik Rahaju; Indah Prabawati (Madani: Jurnal Ilmiah Multidisiplin, 2026)
The implementation of the traditional market revitalization policy at Karah Baru Market in Surabaya City still faces a number of problems, namely suboptimal facilities and infrastructure, illegal kiosk trading practices, and a decline in the number of consumers after revitalization. The purpose of this study is to describe the implementation of the traditional market revitalization policy at Karah Baru Market in Surabaya City. The research method applied is descriptive qualitative, focusing on six policy implementation indicators according to the Van Meter and Van Horn model, including standards and goals, resources, characteristics of the implementing organization, implementer disposition or attitudes, inter-organizational communication and implementer activities, and social, economic, and political conditions. Data collection in this study was conducted through interviews, observation, and documentation. The data analysis technique uses the Miles and Huberman data analysis model, which includes data reduction, data presentation, and conclusion drawing stages. The research results indicate that five implementation indicators have been optimally executed, while the resource indicator has not been optimally met, particularly regarding human resources and facilities and infrastructure. Therefore, strengthening human resource capacity, improving supervision, and perfecting supporting facilities are necessary to ensure the optimal implementation of the policy to revitalize traditional markets.